2018
DOI: 10.1111/jce.13451
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking causes a worse long‐term outcome in persistent atrial fibrillation following catheter ablation

Abstract: Smoking increases the incidence of NPV triggers in patients with persistent AF. Smokers who have RA-NPV triggers during index procedure do have a worse outcome after catheter ablation, indicating the harmful effects of nicotine to right atrium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 48 publications
1
15
0
2
Order By: Relevance
“…Rapid activities were observed in the superior vena cava (SVC) and atrial fibrillation was terminated after SVC isolation. The importance of nonpulmonary vein ectopic foci initiating atrial fibrillation has been documented in numerous literatures, including triggers from the SVC, left atrial free wall, appendage, crista terminalis, coronary sinus, ligament of Marshall, and interatrial septum [1,[4][5][6][7][8]. In our laboratory, we found that the incidence is higher (45%) among patients with longstanding persistent atrial fibrillation who received catheter ablation [7].…”
Section: Nonpulmonary Vein Ectopy In Persistent Atrial Fibrillationmentioning
confidence: 50%
See 1 more Smart Citation
“…Rapid activities were observed in the superior vena cava (SVC) and atrial fibrillation was terminated after SVC isolation. The importance of nonpulmonary vein ectopic foci initiating atrial fibrillation has been documented in numerous literatures, including triggers from the SVC, left atrial free wall, appendage, crista terminalis, coronary sinus, ligament of Marshall, and interatrial septum [1,[4][5][6][7][8]. In our laboratory, we found that the incidence is higher (45%) among patients with longstanding persistent atrial fibrillation who received catheter ablation [7].…”
Section: Nonpulmonary Vein Ectopy In Persistent Atrial Fibrillationmentioning
confidence: 50%
“…recurrence arrhythmia [12]. Recently, we also found that cigarette smoking can increase the incidence of nonpulmonary vein triggers among patients with persistent atrial fibrillation, especially of right atrial nonpulmonary vein triggers and was associated with a worse ablation outcome [5].…”
Section: Key Pointsmentioning
confidence: 99%
“…Smoking increases the incidence of nonPV triggers in patients with persistent AF. Smokers who had arrhythmia triggers located in the right atrium had a worse outcome after ablation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking cessation after AF diagnosis appears to reduce AF recurrence risk [ 102 ] as well as the recurrence risk after pulmonary vein isolation (PVI) [ 113 , 114 , 115 ] and cardioversion, at least for women [ 116 ]. Conflicting data exist regarding the AF risk of former smokers, with some studies showing a reduced AF risk for former smokers compared to current smokers [ 103 , 117 ], whereas other studies could not confirm this finding [ 98 ].…”
Section: Atrial Myocardium and Tobacco Smokingmentioning
confidence: 99%